Effects of social stress on performance and strain in complex multiple task environments. Issue 9 (1st September 2020) - Peifer, Corinna; Sauer, Juergen; Antoni, Conny H.
Abstract: While stress has been an important research area in the field of ergonomics, research on social stress and on the combination of stressors is largely lacking. This study examined the effects of social stress on psychological and physiological strain and performance. As an exploratory research question we looked at the combined effects of social stress and noise. Fifty-one male student participants were tested for 2 h using a computer-based simulation of a process control environment with multiple tasks. Social stress (TSST) and noise (80 dB) were varied experimentally. During the task, we repeatedly measured primary and secondary task performance, subjective strain, and psychophysiological strain (cortisol, heart rate). We found a main effect of social stress on physiological strain, both on cortisol and heart rate, but no main effects of social stress on subjective strain and performance. These results suggest that maintaining performance under stress comes at the cost of physiological strain. Practitioner summary: Although the presence of social stress is common at work, little experimental work has been done. Our experiment provides empirical evidence for negative effects of social stress on physiological stress responses while subjective strain and performance decrements could not be detected. Abbreviations: ANOVA: analysis of variance; b/min: beats per minute; CAMS: cabin air management system; CO2: carbon dioxide; dB: decibel; Df: degrees of freedom; ECG: electrocardiography; h: hours; Hz: hertz; M: mean; min: minutes; N: sample size; nmol/l: nanomol per liter; O2: oxygen; pm: post meridiem; SD: standard deviation; SE: standard error; sec/s: seconds; TSST: trier social stress test